Migration and intercultural conflict: from the rising sun to the land of Pachacamac - Otta Rivera, Vicente (2020)
Explore and reflect on the social world of Japanese migrants in oligarchic Peru. Analyze the context and formation of the nissei community through the history of his father’s unique life and the process of construction of a cultural identity that marked the history and current family memory.